Pengaruh Karakteristik Peternak dan Dukungan Penyuluhan Terhadap Kemampuan Teknis Beternak Sapi Potong di Kecamatan Insana Induk - Sevisko V. Leleng; Agustinus A. Dethan; Ture Simamora (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2021)
This research was conducted to determine the characteristics of farmers and the effect of counseling support on the technical ability of raising beef cattle. This research was conducted in October 2019 in Fatoin Village and Manunain B Village, Insana District, North Central Timor Regency. The research was conducted at the Matani Farmer's Group in Manunain B Village with 14 members and the Ataubale Nunusili Farmer's Group in Fatoin Village with 16 members. The total respondents used in this study were 30 people. The types of data used in this study are qualitative data and quantitative data with the data sources used in the form of primary data and secondary data. Data was collected through observation and interviews with respondents. The results showed that the technical ability of the breeder was strongly influenced by the characteristics of the breeder (age, education, and experience) and extension support (method suitability, media suitability, and extension competence).